Sistem Penempatan Satu Kanal sebagai Strategi Pemerintah Indonesia terhadap Pekerja Migran Indonesia di Arab Saudi - Azizah, Aulia; Wirawan, Rendy; Yuniarti, Yuniarti; Alexandra, Frisca (Department of International Relations, Universitas Mulawarman, 2023)
Problems related to Pekerja Migran Indonesia (PMI) or Indonesian migrant worker occurs frequently in their working countries, on of them is Saudi Arabia. The country has the highest number of problems in relations to PMI. Therefore, Indonesian government by 2015 put moratorium of sending PMI to Saudi Arabia into force. Yet, this policy generated a new problem in which more PMI flew to Saudi Arabia illegally. Thereafter, in 2018 government issued a policy called Sistem Penempatan Satu Kanal (SPSK). This research aims to observe how was the implementation of SPSK by looking through system theory. As the result, SPSK policy yet successful because the implementation was not quite effective due to several impediments.